The Faktor-Faktor Yang Mempengaruhi Pencegahan Fraud Pengelolaan Dana Desa - Suharni, Siti; Wibisono, Nurharibnu; Dianti, Pramita Mawar (INVENTORY: JURNAL AKUNTANSI, 2024)
This research is a quantitative research type. This research aims to examine the influence of the Internal Control System (SPI), Village Apparatus Competency (KAD) and Morality on preventing fraud in Village Fund management in villages in Ngariboyo District, Magetan Regency. The population in this study were all villages in Ngariboyo sub-district. The sampling technique uses purposive sampling. Data was obtained from respondents through distributing questionnaires. Data analysis used multiple linear regression tests with SPSS tools. The results of the analysis show that SPI has a significant positive effect on fraud prevention, KAD has a significant positive effect on fraud prevention. Morality has a significant positive effect on preventing fraud in managing village funds. Simultaneously SPI, KAD, and morality influence the prevention of fraud in village fund management. The results of this research are important in line with the increase in Village Funds from year to year and efforts to distribute Village Funds so that they are right on target.